Improving Insomnia in Primary Care Patients a Randomized Controlled Trial of Nurse-Led Group Treatment: A Literature Review - Alwan Revai (D'Nursing and Health Journal (DNHJ), 2020)
Introduction: Insomnia is generally defined as complaints of poor or unsatisfactory sleep, which can include difficulty initiating sleep, awakening after sleep onset, poor sleep quality, early morning awakenings, short sleep times, short total sleep times and daytime consequences. Chronic insomnia is a common problem in primary health care, affecting 10 - 19% of those seeking primary care. Method: Patient is a randomly selected sample of 165 people and divided into 2 groups, namely 90 treatment groups and 75 control groups in seven routine primary health care in Stockholm County, Sweden between August 2011 and June 2014. The intervention to be given was in the treatment group given the intervention consisting of a group treatment program for insomnia based on the CBT-I technique while the control group was free to undergo insomnia treatment as usual. Result: The formulation of the research problem is to compare how the effect of nurse-led group treatment with the effect of treatment as usual in routine primary health care in Stockholm County, Sweden. In this study, the researcher determined a sample of 165 people who met the research requirements, and divided respondents randomly (single-blinded) consisting of 90 treatment groups and 75 control groups. Conclusion: There was a significant difference between the treatment of insomnia with cognitive therapy and the treatment of insomnia with drugs. So that we can reduce the long-term effects of using drugs to treat insomnia.